Prevalencia de vibrios patógenos en camarón de comercio minorista en mercados del cantón Manta - Intriago Bermúdez, Dariel (2020)
Outbreaks of foodborne diseases are transmitted daily worldwide, and bacteria of the genus Vibrio are a major cause of conditions transmitted by marine food. This represents an ongoing threat for consumers’ food security. The objective of this work was to determine the prevalence of potentially pathogenic bacteria of the genus Vibrio in retails of shrimp in markets in the city of Manta, ManabÍ, Ecuador. For this, the Central Market of Manta, Playita Mia and Eloy Alfaro were characterized using a checklist according to norm INEN 2687: 2013 healthy markets, and the detection of potentially pathogenic Vibrio was perfomed by realtime quantitative PCR microbiological tests, AOAC RI method 050902. The overall percentage of quality in all markets (48.8%) was below the expected minimum (70.0%), and was reflected in significant differences (p <0.05) in the level of compliance with the norm referred to. Among the three Vibrio species evaluared, V. cholerae showed the highest average prevalence (69.7%), V. parahaemolyticus achieved an average prevalence of 49.2%, while V. vulnificus had a low prevalence (10.0 and 3.3%). The prevalence of potentially pathogenic Vibrios did not differ significantly among markets for the three Vibrio species evaluated (p> 0.05). It is concluded that there was a high prevalence of Vibrio species in the shrimp samples from the three seafood retail markets of the Manta municipality.